Scuticociliatosis caused by uronema sp. In ten different ornamental aquarium reef fish in Brazil - Cardoso, Pedro Henrique Magalhães; Moreno, Luisa Zanolli; Moreno, Andrea Micke; Balian, Simone de Carvalho; de Oliveira, Carolina Helena; Soares, Herbert Sousa; Martins, Maurício Laterça; Rodrigues, Marianna Vaz [UNESP] (FapUNIFESP (SciELO), 2020)
Scuticociliatosis, caused by an opportunistic ciliate protozoan, is responsible for significant economic losses in marine ornamental fish. This study reports the occurrence of Uronema spp., parasitizing ten species of marine reef fish at an ornamental fish wholesaler: Blue green damselfish (Chromis viridis), Vanderbilt’s Chromis (Chromis vanderbilti), Pennant coralfish (Heniochus acuminatus), Threespot angelfish (Apolemichthys trimaculatus), Goldspotted angelfish (Apolemichthys xanthopunctatus), Sea goldie (Pseudanthias squamipinnis), Orchid dottyback (Pseudochromis fridmani), Threadfin butterflyfish (Chaetodon auriga), Vagabond butterflyfish (Chaetodon vagabundus), and Bluecheek butterflyfish (Chaetodon semilarvatus). Diseased fish showed disorders such as hemorrhages and ulcerative lesions on the body surface. Histopathological analysis of the muscle, liver, gut, kidney, spleen, gills, and stomach revealed hemorrhages and degeneration of muscle fiber, vacuolar degeneration of hepatocyte, inflammatory process and granuloma in the liver, atrophy of intestinal villi, inflammatory process and granuloma in the kidney, melanomacrophage centers, as well as inflammatory process in the spleen, epithelial cells hyperplasia and granuloma formation in the gills, and vacuolar degeneration and eosinophils in the stomach. Due to the severity of the disease, it is necessary to implement biosecurity measures with rapid and accurate diagnosis to minimize the risk of economic losses caused by Uronema spp.
Scuticociliatose causado por uronema sp. Em dez diferentes peixes ornamentais de recife no Brasil
Keywords: Fish health; Histopathology; Ornamental reef fish; Scuticociliatia